2001
DOI: 10.1080/10903120190939751
|View full text |Cite
|
Sign up to set email alerts
|

C Haracteristics of F Atal a Mbulance C Rashes in the U Nited S Tates : A N 11- Year R Etrospective a Nalysis

Abstract: Most crashes and fatalities occurred during emergency use and at intersections. The greater burden of injury fell upon persons not in the ambulance. Rear compartment occupants were more likely to be injured than those in the front. Crash and injury reduction programs should address improved intersection control, screening to identify high-risk drivers, appropriate restraint use, and design modifications to the rear compartment of the ambulance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
82
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(88 citation statements)
references
References 5 publications
4
82
1
1
Order By: Relevance
“…Other studies have also suggested that the benefits of emergency driving are limited because the transportations are considered to be more or less dangerous for fellow road users, ambulance staff and patients (Kahn et al, 2001;Lawrence, 1994;Solomon, 2003). Accident studies show that most ambulance accidents in urban areas are collisions in intersections (Albertsson and Bylund, 2009;Kahn et al, 2001;Petzäll, 2006;Solomon, 2003). The most common ambulance accidents in rural areas are ambulances that run off the road or collide with other vehicles.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Other studies have also suggested that the benefits of emergency driving are limited because the transportations are considered to be more or less dangerous for fellow road users, ambulance staff and patients (Kahn et al, 2001;Lawrence, 1994;Solomon, 2003). Accident studies show that most ambulance accidents in urban areas are collisions in intersections (Albertsson and Bylund, 2009;Kahn et al, 2001;Petzäll, 2006;Solomon, 2003). The most common ambulance accidents in rural areas are ambulances that run off the road or collide with other vehicles.…”
Section: Discussionmentioning
confidence: 97%
“…Nilsson (2004) has shown that the number of injury accidents change according to the square of the relative speed change. Traffic accidents also occur during ambulance transportation, both in emergency use and non-emergency use, and several studies reveal that emergency driving at high speed is more risky and cause more accidents than non-emergency driving (Becker et al, 2003;Kahn et al, 2001;Lundälv, 2005;Maguire and Porco, 1997;Petzäll, 2006;Solomon, 2003). Emergency driving at high speed is also a stressful situation for patients and personnel, as well as for the driver.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Predictors of low back pain in other health professions have been well documented [Smedley et al, 1997[Smedley et al, , 1998Edlich et al, 2005]; however, EMS is unique in that medical care is often provided in varying and often dangerous locations [Kahn et al, 2001;Maguire et al, 2002;Becker et al, 2003;Proudfoot et al, 2003]. These varying work conditions may impact the susceptibility of EMS professionals to injury.…”
Section: Introductionmentioning
confidence: 96%